Hydrate Formation/Dissociation in (Natural Gas + Water + Diesel Oil) Emulsion Systems - Chang-Yu Sun; Bao-Jiang Sun; Guang-Jin Chen; Huang Liu; Chang-Sheng Xiang; Bao-Zi Peng (Energies, 2013)
Hydrate formation/dissociation of natural gas in (diesel oil + water) emulsion systems containing 3 wt% anti-agglomerant were performed for five water cuts: 5, 10, 15, 20, and 25 vol%. The natural gas solubilities in the emulsion systems were also examined. The experimental results showed that the solubility of natural gas in emulsion systems increases almost linearly with the increase of pressure, and decreases with the increase of water cut. There exists an initial slow hydrate formation stage for systems with lower water cut, while rapid hydrate formation takes place and the process of the gas-liquid dissolution equilibrium at higher water cut does not appear in the pressure curve. The gas consumption amount due to hydrate formation at high water cut is significantly higher than that at low water cut. Fractional distillation for natural gas components also exists during the hydrate formation process. The experiments on hydrate dissociation showed that the dissociation rate and the amount of dissociated gas increase with the increase of water cut. The variations of temperature in the process of natural gas hydrate formation and dissociation in emulsion systems were also examined.